The Ottoman Bosnian Uprising Empire and The Bosnian Uprising : Janissaries, Modernisation and Rebellion in the Nineteenth Century - Turhan, Fatma Sel (I.B. Tauris, 2014)
During my Masters degree study on the abolition of the janissary corps and its repercussions in 1826, I placed special emphasis on the provincial responses to the abolition. At the same time I realized that, among the Ottoman provinces, Bosnia showed the strongest reaction in that its cities and districts were not pacified for a long time. Even a short perusal of archival documents showed that the period of rebellion followed a fluctuating line, with short periods of suppression, followed by recurring reactions. In addition, these reactions were not limited only to ‘the professional janissaries’, but almost all members of the various strata of society took an active part in the rebellion. When I broadened my research, I realized that the Bosnians were not only against the abolition of the janissary corps, but were also uncomfortable about the changes brought about by the centralization and reform policies of the state in general. In terms of local issues, centralization and reform meant a new army for the Bosnians as well as a new land system, a new administration, a change in the status of non-Muslims to the disadvantage of Muslim Bosnians and the establishment of a more interventionist state than before. The reaction of the Bosnians against the centralization policies took the form of outbreaks of rebellion against the Ottoman centre. This reactionary position of Bosnia drove me to study the topic further.